Synthesis and Characterization of Chitosan-Polyvinyl Alcohol-Fe2O3 Composite Membrane for DMFC Application - Permana, Dian; Ilimu, Edi; Faariu, Nur Mala; Setyawati, Arini; Kadidae, La Ode; Ramadhan, L.O.A.N. (Makara Journal of Science, 2020)
This study investigates the utilization of different compositions of Fe2O3 and polyvinyl alcohol (PVA) to modify chitosan in order to prepare a composite membrane. The membranes were synthesized using the phase inversion method and extensively characterized by Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), mechanical properties analysis, and water uptake analysis, whereby SEM was used to confirm the morphology of the composite membranes. Diﬀerent electrochemical properties such as ion exchange capacity, proton conductivity, and methanol permeability of these membranes were also measured. The results showed that increasing the PVA mass improved the water uptake, ion exchange capacity (IEC), and proton conductivity because the PVA addition increased the hydrophilicity of the membrane; thus, the pore surface on the membrane was more open, which also caused higher membrane permeability. However, the methanol permeability values of all composite membranes were lower than that of Nafion. The highest IEC and proton conductivity were obtained for the CS-PVA-H3070 membrane, with values of 4.300 meq/g and 6.71 × 10−2 S·cm−1, respectively. The mechanical strength of these membranes showed that the PVA addition increased the elongation break and decreased the tensile strength of the membrane. The results imply that the chitosan membrane modified with PVA and Fe¬2O3 has a potential for DMFC applications.